Analisis Isi Video Di Media Sosial Channel Youtube Kinderflix Dalam Kasus Pelecehan - Istialdi Pratama Haris; Arfian Suryasuciramdhan; Leo Feni Agustina; Muhammad Salim Al-bana (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2024)
The development of information technology, especially through social media platforms such as YouTube, has rapidly influenced the dynamics of social life in Indonesia. However, along with this growth comes new challenges, especially regarding harassment and negative comments on these platforms. This research takes a case study of the YouTube channel Kinderflix, which provides educational content for children, to explore the impact of abusive comments on content creators. The research results show that negative comments not only have a significant emotional but also psychological impact, especially on content creators. Protection of content creators and more effective management of content on social media platforms is becoming increasingly important. In the context of children's content, the protection of content creators and the welfare of children must be a top priority.